Position of gymnast relative to the vaulting horse during postflight - McNitt-Gray, J.; Mathiyakom, W.; Requejo, P.; Costam, K. (coachesinfo.com)
The article bases on Kinematics Observed during Women's Gymnastics Competition during Sydney 2000 Olympic Games. The purpose of this paper is to: 1) determine the location of the hands/feet of female gymnasts as they passed by the horse during the post flight phase of vaults performed during 2000 Olympic competition, 2) determine the implications of lengthening the vaulting horse on the ability of female gymnasts to clear a longer vaulting apparatus during the post flight phase, 3) identify expected modifications in vaulting technique to accommodate increases in vaulting apparatus length. Methods Vaults (n=140) performed by female gymnasts during the Team Competition of the Sydney 2000 Olympic were video taped ( 60Hz, SONY). A clearance margin was constructed around the end of the horse in the region above and in the direction of travel. This clearance margin around the horse was equal to 1 times the height and width of the superior aspect of the horse ( Figure 1,2). The flight phase of the vaults were then examined to determine if a gymnast's feet or head passed through the clearance margin around the horse at progressively longer lengths in the direction of travel ( 1 to 8 times current length). Passing through the clearance margin at a particular horse length indicates the gymnast may collide or nearly miss the horse during the postflight phase. These results assume that 1) the gymnast will continue to place their hands close to the board end of the vaulting table when vaulting over longer tables and 2) the gymnasts will have the same TBCM position and momentum at the time of horse departure. The ability to clear a longer horse using the same horse departure kinematics observed during Olympic competition were determined by dividing the number of gymnasts that passed through the clearance margin at a particular horse length by the number of vaults examined. Results & Discussion Increasing the horse length by a factor of three will require a significant number (~30%) of female gymnasts to modify either their preflight or postflight mechanics. The results indicate that if the horse length was increased by a factor of three, the head (25%) or feet (35% ) of the female gymnasts competing in the Sydney 2000 Olympic Games would pass within the clearance margin around the horse (Figure 1,2). Even at the current horse length, female gymnasts competing in the Olympic Games collided with the horse either with their feet or their heads (Figures 1,2). From previous research conducted during elite gymnastics competitions, it is not likely that female gymnasts will be able to generate significantly greater TBCM horizontal velocity during the run-up phase of the vault. Female gymnasts using a longer vaulting table will need to modify the preflight or postflight mechanics they currently use when vaulting over the horse so that they can consistently clear the apparatus with adequate momentum to successfully land the vault. Preflight modifications in initial hand placement toward the far end of the vaulting table will enable the gymnast to place their TBCM closer to the end of the vaulting table at the time of departure. Female gymnasts vaulting over a longer vaulting table may also need to modify their body position at the time of initial horse contact. Modifying the initial body position at the time of contact typically influences the magnitude and direction of the linear and angular momentum at apparatus departure. The clearance margin around the end of the vaulting table may also be increased by modifying body segment configurations (e.g. tuck, pike, layout) at the time the gymnast passes by the end of the vaulting table. Changes in the apparatus geometry and/or mechanical properties of the apparatus will likely influence the momentum generated and the loading experienced by the body during the hand/horse interaction. Additional research is needed to determine how modifications in the mechanical properties of the vaulting table will change the loading experienced by the body, the magnitude of the total body momentum at vaulting table departure and/or the post flight duration.